Influence of cypermethrin on avoidance behavior, survival and reproduction of Folsomia candida in soil - Zortea T.* (2015)
© 2014 Elsevier Ltd.Cypermethrin is a pyrethroid widely used in agriculture and in control of animal ectoparasites, being effective against a large number of insects. Therefore, this study aimed to evaluate the effects of cypermethrin on soil fauna using reproduction and behavior ecotoxicological tests with the springtail Folsomia candida. The surface layer of a soil characteristic of the western region of the Santa Catarina State, classified as Typic Dystrupept, was used as test substrate. The treatments on both tests consisted of five concentrations of cypermethrin (0, 7.5, 15.0, 22.5, and 30.0mgkg-1) corresponding to 0, 1.5, 3.0, 4.5, and 6.0gm-2, respectively. This range was chosen according to technical instruction for the use of this product in broilers beds (that are used afterwards as organic fertilizer in soil) that recommends 15mgkg-1 (3.0gm-2). The results obtained with tests for F. candida showed toxicity at all doses tested, following a dose-related response resulting in reduction in survival rate (LC50 of 18.41mgkg-1, equivalent to 3.8gm-2), in the number of juveniles (EC50 of 15.05mgkg-1, corresponding to 3.01gm-2), and an increase in avoidance response (AC50 of 29mgkg-1, corresponding to 5.8gm-2). Although more studies are needed focusing on the fate of cypermethrin in soil when the poultry beds are used as fertilizer and how it may affect soil fauna, data obtained in this study, by showing effects within the range of the doses that are recommended implies that caution and possible mitigation measures should be taken when using this compound.